2005
DOI: 10.1177/101053950501700205
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Load and Macronutrient Intake in Healthy Italian Children

Abstract: The objective is of this study is to examine the relationship of dietary glycemic load (GL) and overall glycemic index (OGI) with macronutrients intake, body mass index (BMI) and insulin sensitivity in healthy children. The subjects comprised of 105 healthy non-obese eight-years old children, 60 boys and 45 girls. A Food Frequency Questionnaire (FFQ) evaluating dietary habits, GL and OGI. Insulin sensitivity was evaluated by the homeostatic model assessment (HOMA). GL was positively associated with dietary tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As a first step, we have assessed the dietary intakes in a population of CF patients regularly followed up at our CF Center. To this aim, we have used a foodfrequency questionnaire that, in other nutritional studies (27)(28)(29)36,37), permitted us to correlate early adiposity rebound (27,36), plasma fatty acids (28) and overall glycemic index (29,37) with dietary macronutrient intakes (protein, animal foods, and carbohydrate, respectively) from early infancy through later childhood. By using the same questionnaire in the present investigation, we could examine for the first time the plasma fatty acid status in relation to dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step, we have assessed the dietary intakes in a population of CF patients regularly followed up at our CF Center. To this aim, we have used a foodfrequency questionnaire that, in other nutritional studies (27)(28)(29)36,37), permitted us to correlate early adiposity rebound (27,36), plasma fatty acids (28) and overall glycemic index (29,37) with dietary macronutrient intakes (protein, animal foods, and carbohydrate, respectively) from early infancy through later childhood. By using the same questionnaire in the present investigation, we could examine for the first time the plasma fatty acid status in relation to dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Among children aged 8 years, a high GL diet reflected a poorer quality diet, including high intakes of white bread and sweetened baked goods and low intakes of fiber, fruit and vegetables. 139 In a seminal crossover study, David S. Ludwig et al 140 observed an 81% greater voluntary energy intake after a high-GI meal compared to low-GI meal among obese boys aged 12 years; the study also showed that the high GI meal resulted in higher serum insulin level, lower plasma glucagon, lower post-absorptive plasma glucose and serum free fatty acids, and elevation in plasma epinephrine, all of which may promote excessive food intake. 141 Likewise, greater energy intakes at lunch were observed among both overweight and normal weight children aged 9-12 years after consuming a high-GI breakfast compared to a low-GI breakfast.…”
Section: Glycemic Indexmentioning
confidence: 99%
“…For example, some researchers have shown a positive relationship between dietary intake of CHO and fat in AA (16)(17)(18), but not European children (19). Further, a relationship between fat intake (but not CHO intake) and the insulin sensitivity index (SI) in EA and HA adolescents has been observed (20), but neither dietary fat nor CHO was associated with SI in a prepubertal subset of their cohort (21), implying the possibility of an effect of maturation status.…”
Section: Introductionmentioning
confidence: 99%